Tea consumption and risk of type 2 diabetes mellitus: a systematic review and meta-analysis update - Yang, Jian; Mao, Qun-Xia; Xu, Hong-Xia; Ma, Xu; Zeng, Chun-Yu (BMJ open, 2014)
Objective Tea has been suggested to decrease blood glucose levels and protect pancreatic β cells in diabetic mice. However, human epidemiological studies showed inconsistent results for the association between tea consumption and type 2 diabetes mellitus (T2DM) risk. The aim of this study was to conduct a meta-analysis to further explore the association between tea consumption and incidence of T2DM. Design Systematic review and meta-analysis. Methods We performed a systematic literature search up to 30 August 2013 in PubMed, EMBASE, Chinese Wanfang Database and CNKI database. Pooling relative risks (RRs) were estimated by random-effect models. Two kinds of subgroup analyses (according to sex and regions) were performed. Sensitive analyses were performed according to types of tea. Results Overall, no statistically significant relationship between tea consumption and risk of T2DM was found based on 12 eligible studies (pooling RR 0.99, 95% CI 0.95 to 1.03). Compared with the lowest/non-tea group, daily tea consumption (≥3 cups/day) was associated with a lower T2DM risk (RR 0.84, 95% CI 0.73 to 0.97). Subgroup analyses showed a difference between men and women. Overall, the RRs (95% CI) were 0.92 (0.84 to 1.00) for men, and 1.00 (0.96 to 1.05) for women, respectively. Tea consumption of ≥3 cups/day was associated with decreased T2DM risk in women (RR 0.84, 95% CI 0.71 to 1.00). Overall, the RRs (95% CIs) were 0.84 (0.71 to 1.00) for Asians, and 1.00 (0.97 to 1.04) for Americans and Europeans, respectively. No obvious change was found in sensitivity analyses. Conclusions The results suggest that daily tea consumption (≥3 cups/day) is associated with a lower T2DM risk. However, further studies are needed to enrich related evidence, especially with regard to types of tea or sex.